Detection, quantification, and profiling of PSA: current microarray technologies and future directions. Issue 9 (19th January 2016) - Sonawane, Mukesh Digambar; Nimse, Satish Balasaheb; Song, Keum-Soo; Kim, Taisun
Abstract : The death rate of 13% among the men diagnosed with prostate cancer makes it a second leading cause of cancer death. This critical review evaluates DNA and protein microarray based methods for detection, quantification, and profiling of PSA. Abstract : Prostate cancer (PCa) is a cancer of the prostate gland. The death rate of 13% among the men diagnosed with PCa makes it the second leading cause of cancer death. It has been reported that the monitoring of the progression of PCa and response to therapy is done by measuring the level of blood PSA. Even though PSA has been used for the diagnosis of PCa, the current scenario dictates the necessity of simultaneous detection of more than one biomarker. This critical review evaluates the DNA microarray and protein microarray based methods reported in the last five years for the detection, quantification, and profiling of PSA.